HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN KUALITAS HIDUP LANSIA DI DESA CEBONGAN SLEMAN YOGYAKARTA TAHUN 2015 - Ririh Antari, Bayu; Saktika, Tetra; Ferianto (MEDIA ILMU KESEHATAN, 2016)
Background:Elderly period is a part of growth process. During this time,elderly will gradually experiencephysical, mental and social degeneration. Elderlywill alsoencounterseveral health problems including blood vessel disorders, metabolic disorders, joint disorders, and psycho-social disorders. The elderly welfare is assessed from their quality of life. Quality of life is used widely as anindication of the psychological welfare of elder age. Objective: To investigate the relationship between social support and quality of life of the elderly in the village of Cebogan, Sleman Methods: This study was quantitative descriptive research with cross sectional approach. The population in this study was the elderly in the village of Cebongan, Sleman, Yogyakarta. Sampleswere chosenwith random sampling. The data analysis used Pearson product moment. Results:Elderly in the village of Cebongan, Sleman, were mostly aged 60-70 years old, and male. Social support which was givenwasof average 3.87 (SD= 0.329). Quality of life of the elderly was of average values as follows; physical quality of 65.31, psychology quality of 62.47, social quality of 70.14, environmental quality of 65.48, and cumulative quality of 65.85 (SD= 11.531). The result of Pearson Product examination figured out p= 0,000<0,05 with correlative coefficient value of 0,616. Conclusion: There was a relationshipbetween social support and quality of life of the elderly in the village of Cebongan, Sleman, with closesignificance level. Keywords: Social Support and Quality of Life